Determinants of Return’s Co-Movement for Effective Portfolio Diversification Among Regional Stock Markets - Rehman, Mobeen Ur; Shah, Syed Muhammad Amir (Revista Evidenciação Contábil & Finanças, 2016)
This paper investigates empirically the linkage between frontier and emerging markets of Asia with the developed markets of Unites States, Japan and Europe over the period of 15 years from January 2000 to December 2014. To deal with heterogeneous panels, we have made use of pooled mean group statistics suggested by Pesaran et al. (2001) for more reliable results. After testing for panel unit root and co-integration, both short and long term relationship were found among the included markets thereby supporting the feedback hypothesis. The direction of relationship is more important from developed to emerging and frontier markets than among the developing-emerging markets. Results suggest that integration is higher among EFA and Japanese markets than the EFA and US markets. These findings are in accordance with the view that level of stock market integration continues to increase. The finding of this paper has important implication for the researchers, practitioners and policy makers. Knowledge about the kind of relationship between EFA and developed markets can help governments of EFA markets to devise various strategies keeping in view their return sensitivity to the developed equity markets. This can help in predicting the return pattern of emerging and frontier markets over the period of short and long run. Furthermore, the relationship among EFA and developed markets enable investors to reap maximum diversification benefits and to minimize risks due to financial contagion or spillover phenomena.